Tindak Pidana Penipuan dan Pencucian Uang dalam Putusan Nomor :1221/Pid.B/2020/PN JKT.SEL - Aldi Raharjo; Suriadi Bangun; Hasudungan Sinaga (Pusat Riset dan Inovasi Nasional, 2024)
Fraud and money laundering are two forms of economic crime that harm many parties, both individuals and institutions. In order to combat and eradicate these crimes, law enforcement authorities often face difficulties in securing and recovering assets obtained from illegal activities. Therefore, the use of asset confiscation mechanisms becomes crucial in an effort to restitute victims and recover illicitly obtained funds.This thesis examines the practical legal challenges faced by the legal system in confiscating criminal assets. These include the process of investigation and gathering valid evidence, as well as the challenges of dealing with concealment and diversion of assets by criminals. Limited resources and differences in legal systems between countries are also factors that affect effective asset forfeiture.Next, the author reviews various strategies and policies that can be implemented to improve the efficiency of confiscating criminal assets. The main focus includes increased cooperation between law enforcement agencies, the use of modern technology in asset analysis and tracking, as well as efforts to raise public awareness about the importance of returning illegally obtained assets.Finally, the author presents decision Number: 1221/Pid.B/2020/PN JKT.SEL or a successful case in conducting asset confiscation for fraud and money laundering. These cases provide valuable lessons on effective tactics and strategies in facing the challenges of economic crime.In conclusion, asset forfeiture is an important tool in the fight against fraud and money laundering. Through greater international cooperation, improved legal systems, and the implementation of appropriate strategies, it is hoped that asset recovery efforts related to economic crime can become more successful and have a positive impact on victims and society as a whole.